PENGEMBANGAN MODEL PEMBELAJARAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN KETERTARIKAN BELAJAR MATEMATIKA - Akmal Hi Dahlan (Jupitek)
This study aims to increase students' interest in learning mathematics. Based on the results of the pre-study, it was found that students were less interested in mathematics learning. This is caused by several factors including (1) mathematics learning so far generally lacks opportunities for students to develop strategic thinking skills, teachers only emphasize students to memorize all formulas or concepts without understanding their meanings, (2) learning is centered to the teacher (the use of lecture methods in mathematics learning) so that students are only used as learning objects, (3) in learning teachers rarely deliver material in real forms but only in abstract form. Therefore the learning series is designed using the Indonesian Realistic Mathematics Education (PMRI) learning approach to answer the phenomena that occur in pre-research. This study is a qualitative descriptive study. Subjects in this study were students of grade VII-A SMP Negeri 1 Pulau Morotai, North Maluku Province which numbered 25 people. The instruments used in this study were tests and interviews of teachers and students. The results showed that after the PMRI learning model was applied students felt interested and could improve mathematical knowledge and could also increase students' activeness in delivering ideas. For example, students dare to interact and negotiate between students and students and between students and teachers during the learning process. In addition, the PMRI learning approach can also reduce the level of abstractness of students in solving mathematical problems. This kind of thing does not happen to the learning by the mathematics teacher before. As a suggestion for teachers, in mathematics learning teachers should be able to connect the real world with mathematics learning because that can facilitate students to solve mathematical problems, and can increase students' interest in learning mathematics